A case study on functional polymer modification of cacao husk for enhanced removal of nitrate and phosphate from vinasse waste - Nur Aini; Aster Rahayu; Siti Jamilatun; Ilham Mufandi (Case Studies in Chemical and Environmental Engineering)
Cacao husk (CH) is a waste product from Indonesian cacao cultivation and holds potential as an adsorbent. In this study CH was modified using 2-[(methacryloyloxy)ethyl]trimethylammonium chloride (META) for removing nitrate and phosphate ions. The applicability of various adsorption isotherm models (Langmuir, Freundlich, Dubinin-Radushkevich (D-R), and Temkin) was explored, and the chemical structure changes were characterized. The results demonstrate that CH-T-META effectively adsorbs nitrates and phosphates from vinasse waste. The Langmuir isotherm model described the adsorption process excellently, suggesting monolayer adsorption. Fourier-transform infrared spectroscopy (FTIR) analysis revealed the presence of O–H/N–H and CO bonds after vinasse adsorption, indicating potential interaction mechanisms. Additionally, scanning electron microscopy (SEM) and X-ray diffraction (XRD) analyses confirmed structural modifications on the CH-T-META surface. Furthermore, CH-T-META exhibited increased H, C, and N content compared to unmodified CH-T-META. Significantly, CH-T-META achieved a removal efficiency (Re) of approximately 93.4 % for nitrates and 96 % for phosphates. These findings strongly support the effectiveness of META modification in enhancing the adsorption capacity of CH for nitrate and phosphate removal from vinasse waste.